Constructions of neoliberal reason - Peck, Jamie 1962- (Oxford University Press, 2010)
This title examines the rise and diffusion of free-market thinking, from the early 20th century through to the age of Obama. It tracks the ascendency of neoliberalism, its key players and decisive moments of reconstruction, including the Chicago School of economics, Hurricane Katrina, and the Wall Street crisis of 2008